1984
DOI: 10.1037/0022-3514.47.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Individual and structural solutions to resource dilemmas in two cultures.

Abstract: Groups of six subjects, in the United States and Holland, were given a resource management task in which they were to harvest points from a regenerating resource pool. Their objective was to maximize individual harvests while maintaining the resource pool. The factorial design crossed three levels of resource use (overuse, underuse, and optimal use) with two levels of variance of others' purported harvests (low and high). Both variables were manipulated through false feedback to subjects regarding the pool siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 15 publications
7
119
1
1
Order By: Relevance
“…Several models of human resource use (e.g., Brucks, 2004;Mosler & Brucks, 2003;Wilke, 1991; see also Gifford & Hine, 1997) propose that the conservational motive of an individual is particularly strong when the pool is perceived as deteriorating. A large body of research (e.g., Messick et al, 1983;Samuelson et al, 1984) supports this notion with the observation that many people-especially prosocials, as was explained above-adapt to a reduction of pool size by cutting down their consumption. Therefore, we assume that the detrimental effects of noise should be particularly influential when people get the feedback that the resource is in decline, as noise may weaken their motive to preserve the pool from being exhausted.…”
Section: Social Value Orientations and Noise In A Commons Dilemmamentioning
confidence: 74%
“…Several models of human resource use (e.g., Brucks, 2004;Mosler & Brucks, 2003;Wilke, 1991; see also Gifford & Hine, 1997) propose that the conservational motive of an individual is particularly strong when the pool is perceived as deteriorating. A large body of research (e.g., Messick et al, 1983;Samuelson et al, 1984) supports this notion with the observation that many people-especially prosocials, as was explained above-adapt to a reduction of pool size by cutting down their consumption. Therefore, we assume that the detrimental effects of noise should be particularly influential when people get the feedback that the resource is in decline, as noise may weaken their motive to preserve the pool from being exhausted.…”
Section: Social Value Orientations and Noise In A Commons Dilemmamentioning
confidence: 74%
“…A case in point is that several social dilemma theorists have suggested that people have the goal-besides individualistic and altruistic goals-to preserve the pool from being depleted. An evident indicator for this notion is the repeated observation that many people adapt to a deteriorating pool by substantially cutting down their consumption (e.g., Messick et al, 1983;Samuelson et al, 1984). However, this conservational motivation may be undermined by the presence of noise or repeated experiences thereof.…”
Section: Noise In a Commons Dilemmamentioning
confidence: 99%
“…Past research on the commons dilemma has revealed that many people tend to reduce their consumption when resources are in decline in order to preserve them from being depleted (e.g., Kramer, McClintock, & Messick, 1986;Messick, Wilke, Brewer, Kramer, Zemke, & Lui, 1983;Samuelson, Messick, Rutte, & Wilke, 1984;Wilke, 1991). In a parallel manner, scholars of conservational psychology often observe a general pro-environmental attitude in society (e.g., Dunlap, Van Liere, Mertig, & Jones, 2000;Stern, 2000a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are separate from the laboratory-based commons dilemma "simulations" that use a small number ofreal, rather than simulated, participants. Computer simulation programs have been developed for research on decision making, using fish stocks (Gifford & Wells, 1991;Mosler, 1993) or other limited resources (Birjulin, Smith, & Bell, 1993;Samuelson, Messick, Rutte, & Wilke, 1984) to frame the dilemmas involved. Demonstration modules on commons dilemmas have also been included in packages of computerized lab demonstrations, based on the fisheries (Mind Scope, Henderson, 1991) and other shared resources (PsychSim, Ludwig, 1992;Psychware, Slotnick, 1986; Psychology on a Disk, Shimoff, Catania, & Matthews, 1992).…”
mentioning
confidence: 99%